La escena artística en Quito a inicios del siglo XX: exposiciones, prensa y público (Dossier: Historias críticas del arte; diálogos transdisciplinarios e indagaciones sobre la estructuración del campo artístico) - Pérez Arias, Trinidad (2018)
This text explores the role that art shows, the press, and the public played in organizing a modern art system and as the driving forces behind the art scene in Quito between 1904 and 1918. First of all, it examines the role played by the Fine Arts School in expanding art production, following its reestablishment in 1904. Then it considers the relationship between the visual arts, the public stage, and the establishment of a liberal State and its plan to build a modern society. Finally, it identifies the tensions sustained by this cultural process when new stakeholders arrived on the scene around 1918.